2015
DOI: 10.1038/nature14443
|View full text |Cite
|
Sign up to set email alerts
|

The Xist lncRNA interacts directly with SHARP to silence transcription through HDAC3

Abstract: Many long non-coding RNAs (lncRNAs) affect gene expression1, but the mechanisms by which they act are still largely unknown2. One of the best-studied lncRNAs is Xist, which is required for transcriptional silencing of one X-chromosome during development in female mammals3,4. Despite extensive efforts to define the mechanism of Xist-mediated transcriptional silencing, we still do not know any proteins required for this role3. The main challenge is that there are currently no methods to comprehensively define th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
1,106
5
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 992 publications
(1,150 citation statements)
references
References 45 publications
35
1,106
5
4
Order By: Relevance
“…Interestingly, our RNAi screen targeting splicing factors did not identify any new additional sex determination genes, indicating that there are a limited number of genes yet to be identified in this pathway. Finally, intriguingly, three recent studies have identified SPEN and Rbm15 (the mouse and human ortholog of Nito) as factors interacting with Xist, the long noncoding RNA that is essential for dosage compensation in mammals (36)(37)(38). Clearly, future experiments such as RNA-seq will be necessary to elucidate the mechanism and logic of Nito-mediated signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our RNAi screen targeting splicing factors did not identify any new additional sex determination genes, indicating that there are a limited number of genes yet to be identified in this pathway. Finally, intriguingly, three recent studies have identified SPEN and Rbm15 (the mouse and human ortholog of Nito) as factors interacting with Xist, the long noncoding RNA that is essential for dosage compensation in mammals (36)(37)(38). Clearly, future experiments such as RNA-seq will be necessary to elucidate the mechanism and logic of Nito-mediated signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…The recently described CHART-MS (capture hybridization analysis of RNA targets) (West et al 2014), CHIRP-MS (chromatin isolation by RNA purification) (Chu et al 2015), and RAP-MS (RNA antisense purification) (McHugh et al 2015) are all based on so-called "tiling approaches," which use sets of overlapping biotinylated DNA oligonucleotides that cover the length of the whole transcript. The advantage of the tiling approaches is that RNA integrity is less critical than for specific RNP capture, which uses just one oligonucleotide to capture the RNA of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides have been extensively used to purify specific RNAs and their protein partners (Lamond et al 1989;West et al 2014;Chu et al 2015;McHugh et al 2015), as exemplified by the recent determination of the Xist RNA-bound proteome using biotinylated DNA oligonucleotides covering the entire transcript length (referred to as "tiling approach") (Chu et al 2015;McHugh et al 2015). While such a strategy enables targeting of RNA lacking full integrity, the "tiling approach" cannot be used to analyze distinct transcript isoforms or particular regions of interest from within a given RNA.…”
Section: Introductionmentioning
confidence: 99%
“…First, the most prominent hit was XIST, with all four shRNAs in our library appearing among the most enriched shRNAs in all four replicates of our screen. Second, the largest functional group we identified consisted of eight genes involved in chromatin structure and regulation, including Dnmt1 and HDAC3, which had previously been linked to XCI (19,32). Third, our screen identified 4 of the 13 genes found by Bhatnagar et al (22) in a screen that used a fundamentally different reporter to identify Xi reactivators, namely GFP driven by the CMV promoter.…”
Section: Discussionmentioning
confidence: 97%